Predictors and clinical outcomes of silent hypoxia in COVID-19 patients, a single-center retrospective cohort study. Issue 11 (November 2021) - Alhusain, Faisal; Alromaih, Azam; Alhajress, Ghassan; Alsaghyir, Abdullah; Alqobaisi, Ali; Alaboodi, Talal; Alsalamah, Majid
Abstract: Background: Patients with COVID-19 usually present with fever and respiratory symptoms such as cough, sputum production, and dyspnea. However, they may suffer from severe hypoxemia without a clinical correlation with the respiratory symptoms, also known as silent or apathetic hypoxia. The aim of the study was to assess the predictors and clinical outcomes of COVID-19 patients without dyspnea. Methods: A single-center retrospective cohort study, based on data extracted from the electronic hospital information system, with COVID-19 patients over a 10-month period in Riyadh, Saudi Arabia. Results: Of the COVID-19 patients presenting at the Emergency Department with a SpO2 < 90%, 13% had silent hypoxia. The majority of the patients required BiPAP, 34% were intubated and 60% were admitted to an intensive care unit. There was no association between dyspnea and gender, age group, body mass index, or comorbidity. Cough, fever, and chronic cardiac diseases were predictive for dyspnea in a regression analysis. There was no difference in the clinical outcome between patients with silent dyspnea or dyspnea. Age and obesity were significantly associated with a decrease in survival, and an increase in the initial SpO2 increased survival. Conclusion: Patients with cardiac disease are more likely to present with silent hypoxia. The SpO2 saturation in COVID-19 may be an independent predictor of survival. Silent hypoxia in COVID-19 patients does not appear to have an association with increase in mortality.